Case Study on Urban Atmospheres in Maribor - Donnay, Francois; Prokešová, Zuzana; Svozilová, Anna; Tänzer, David; Vešligaj, Goran; Rothfuss, Eberhard (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
Our research explores how people living in, working in, or visiting Maribor experience different urban areas and the emotions these spaces evoke. We aim to move beyond the physical and functional aspects of cities to understand how the built and social environments shape daily urban experiences. The study focuses on “urban atmospheres” of two contrasting case studies: the Lent waterfront, designed to evoke calm, natural and positive feelings, and the Europark shopping centre, which creates a lively, consumer-driven atmosphere. By comparing these spaces, we aim to identify what makes them feel distinct and how diverse groups of people perceive them. Ultimately, our goal is to highlight the role of urban atmospheres in shaping lived experiences and to contribute insights to the field of urban studies. We emphasise the importance of designing cities that are not only functionally modern but also emotionally and sensory engaging and supportive of human well-being.